Democratize Health Policy Through Citizen’s Charter in North Bengkulu District - Achmad Aminudin (Policy & Governance Review, 2018)
This research is analyzing about how the policy of democratization and regional autonomy can born Citizen’s Charter in public sevice. The purpose of the regional autonomy implementation is to shortening the distance of service among goverment and the society, so the local goverment can understand more about desires, aspirations and needs of the community compared with the central government who has longer distance from the society. The effort to shortening the distance makes the execution of regional autonomy needs some changes and inovations in giving the service in order to match with the society needs. The result of this research shows that the democratization and regional autonomy policy still can’t born the Citizen’s Charter in local public service yet, particularly in health care services contract in the Arga Makmur city, North Bengkulu. Realization of the Citizen’s Charter principles in the Puskesmas Arga Makmur, North Bengkulu district is proved to have different characteristics with the Citizen’s Charter which occurred in Java commonly. In North Bengkulu, the implementation of the Citizen’s Charter not only need strong political will from local goverment, budget support (General Revenue and Expenditure Budget/ APBD), the availability of adequate infrastructure, commitment and quality of the resource officers, community support, the importance of shifting paradigm in society toward formal treatment like Puskesmas, but also need a personal leadership for the head of Puskesmas. Without any initiation from personal leadership, it can be sure that the implementation of Citizen’s Charter in regional seems can’t be running well.